Pengaruh Pemberian Jus Kurma Ajwa Dan Susu Almond Terhadap Kelancaran ASI Pada Ibu Menyusui di TPMB NP Cikarang Timur Bekasi Tahun 2024 - Neneng Julianti; Nia Nurfitria Tsani; Nengsih Patmawati (Bunda Edu-Midwifery Journal (BEMJ), 2025)
Breast milk is important food for babies and the best nutrition because it has the energy and substances needed throughout the first 6 months of a child's life. Giving Ajwa date juice and almond milk is a drink combination of 100 grams or 15 dates soaked in 100ml boiled water and added with 250ml almond milk and blended, filtered and boiled until boiling for 5-10 minutes, consumed once a day for 7 days. This research is to determine the effect of Ajwa Date Juice and Almond Milk on the smooth flow of breast milk in breastfeeding mothers at TPMB Nengsih Patmawati Amd. Keb, Tanjung Baru, East Cikarang, Bekasi 2024. This research uses a Quasi Experimental Design with a One Group Pretest and Post Test Design. The population were all breastfeeding mothers at TPMB Nengsih Patmawati in January-April 2024 with a population of 30 people. The sample used the Total Sampling. The instruments used in this research were questionnaires and observation sheets. The data were analyzed using univariate and bivariate and previously a data normality test with Shapiro Wilk and a non-parametric statistical test, namely the Wilcoxon test. The research results show that an effect of giving Ajwa Date Juice and Almond Milk on the smooth flow of breast milk in breastfeeding mothers with Asymp. Sig <0.001 (P<0.05) so Ha is accepted. The conclusion is that giving Ajwa Date Juice and Almond Milk has an effect on the smooth flow of breast milk to breastfeeding mothers. It is hoped that the results of this research can increase knowledge regarding the influence of Ajwa Date Juice and Almond Milk on the smooth flow of breast milk in breastfeeding mothers and can apply it  and Ajwa Date Juice and Almond Milk will become one of the innovative products in the Midwifery.